A New Paradigm of Engagement for the Socially Distanced Artist. Issue 1 (2nd January 2021) - Frenneaux, Richard; Bennett, Andy
ABSTRACT: COVID-19 has presented many challenges to the music industry and to artists who rely on live music not only as a source of revenue but also as an integral part of their release strategy and audience engagement. It is important to examine the modalities of artistic expression when faced with a new "socially distant" paradigm. This article describes how, while many of the platforms used by independent artists have been in place for years, the COVID pandemic is promoting further disruptive innovation from a technological perspective to meet consumer demand and a deeper and more engaging method of expression cultivated by artists when working remotely from their audience.